Association of complete denture wearing with the rate of reduction of mandibular residual ridge using digital panoramic radiography - Al-Jabrah, Osama Awad; Al-Shumailan, Yousef Rashid (International Journal of Dental Research, 2014)
Background: Residual ridge reduction is one of the main causes of loss of stability and retention of mandibular complete dentures. The severity of bone loss is very important clinical condition facing the aging population. Objectives: To investigate the association of the mandibular ridge reduction with duration of complete denture wearing in relation to age and gender is using digital panoramic radiography. Methods: Seventy-five (40 men and 35 women) with a mean age 66.21±10.21 years, denture-wearing patients were included in this study. Resorption in the mandibular residual ridges was assessed by using the mental foramen and the inferior border of the mandible, as they appear in digital panoramic radiographs, using Wical and Swoope Analysis method. Measurements were performed digitally using Sidexis next Generation software. The amount of resorption was calculated and correlated to gender, age and duration of denture wearing. Statistical analysis was performed using SPSS (V17.0). Level of significance was set at 0.05. Results: The mean ridge resorption was 7.74±5.80 mm (20%), Women significantly (P<0.05).recoded more resorption than men (women: men ratio was 3:2). Men significantly (P<0.0001) had greater mandibular ridge and mental foramen heights than women. Ridge resorption significantly increased with increasing age (P<0.0001) and duration of denture wearing (P<0.001). Women significantly (P<0.05) had greater ridge resorption than men below 50 and above 80 years old; and in all denture wearing duration groups. Conclusion: Reduced mandibular height is directly related to age and duration of complete denture wearing. Women are at more risk to have ridge resorption compared to men. Keywords: Complete denture, mandible, mental foramen, panoramic radiography, residual ridge resorption.